Safety and Gastro protective Activity of Graviola Seeds Extract against Acidified Aspirin Induced Gastric Ulceration - Mays Ali Fadhel (Journal of Global Pharma Technology, 2018)
Peptic ulcer disease attacks millions of people yearly around the globe, affecting both quality and quantity of life. There are many different causes responsible for the etiology of this disease; one of the most common causes is non-steroidal anti-inflammatory drugs (NSAIDs) through different mechanisms. Annona muricata have been found to have antioxidant effects, along with a good protective effect against inflammation in rats, making it a good candidate as a potential gastro protective agent. So, this study is designed to evaluate this possible pharmacological activity. Annona muricata seeds were extracted; chemical analysis of the extract has been done, acute toxicity study has been performed using different doses of ethanolic seed extract of Annona muricata (ESAM) 500, 2000, and 5000 mg/kg, the extract demonstrated relative safety at doses up to 2000mg/kg. The gastro protective effect of ethanol seeds extract of Annona muricata (ESAM) has been investigated using two doses of ESAM 250 and 500mg/kg of ESAM, using ranitidine 50mg/kg, as a reference, ulcer was induced by acidified aspirin solution after 7 days. The extract caused reduction in the gastric content volume, ulcer index and TNF-α, and a significant elevation in the gastric PGE2 and SOD levels in dose dependent manner showing a good preventive index in compare to the acidified aspirin group. Gastro protective effect of ESAM was prevented by pretreatment with sulfhydryl alkylating group (NEM) and NOS inhibitor group (L-NNA) approving the involvement for sulfhydryl (SH) group and endogenous nitric oxide (NO) in the gastro protective effect of Annona Muricata seeds. Immunohistochemical staining showed pretreatment with ESAM caused upregulation of HSP70. So, this study suggests that the seeds extract of Annona muricata is relatively safe. Its gastroprotective activity attributed to its antisecretory; cytoprotective; antioxidant and anti-inflammatory effects.Keywords: Acute toxicity, Annona muricata seed extract, Gastro protective, Non-steroidal anti-inflammatory drugs.